Single Nanocrown Electrodes for High‐Quality Intracellular Recording of Cardiomyocytes - Ching‐Ting Tsai; Hongyan Gao; Csaba Forro; Yang Yang; Viktoriya Shautsova; Xingyuan Zhang; Zeinab Jahed; Bianxiao Cui (Advanced Materials Interfaces, 2025)
Abstract Nanoelectrode arrays (NEAs) are emerging as promising technologies for minimally‐invasive, parallel intracellular recording. These vertical electrodes, typically hundreds of nanometers in diameter and micrometers in height, provide a means for gentle electroporation and reversible membrane permeabilization to achieve intracellular recording. Prior studies have used 5–9 vertical nanostructures per recording channel to enhance device robustness and signal strength. However, this approach complicates the establishment of a one‐to‐one correspondence between cells and electrodes. In this study, devices with recording channels featuring 1‐, 3‐, 5‐, or 9‐ vertical nanocrowns electrode arrays (NcEAs) are developed in the same device. Channels with vertical nanoelectrodes of different geometries, as well as non‐vertical electrodes, such as shallow hole electrodes and large flat electrodes, are also incorporated. These measurements demonstrate that a single NcEA not only provides high‐quality iAP recordings but also excels at preserving the intracellular waveform. In contrast, non‐vertical electrodes detect intracellular‐like signals with distorted waveforms and are not suitable for cardiac intracellular recordings. These findings highlight the critical role of electrode geometry in improving the precision and reliability of intracellular recording technologies.